RSSI Indoor Outdoor Personal Localization: A Study to Found Targeted Social Engineering Victim by Attacker Via Wireless Methods - Firdausi, Ahmad; P. N. Hakim, Galang (Journal of Robotics and Control (JRC), 2021)
Social engineering is a common method to collect more information from victim trough socialization. This method employs human psychology to manipulate other people. In cyber society today, the attacker could use various methods to tapping into victim smartphone, and after that the attacker can get victim persona profiling information. The attacker can select random victim and then using wireless localization methods, the attacker could found its victim. After the random victim has been found the attacker can start social engineering directly to the victim based on persona profiling information, to gain trust and more personal information that can lead inflicting damage to the victim. In this paper, we demonstrate to localize victim using green obaidat calibrate Path loss Propagation models and $4 dollar device based on victim Smartphone RSSI Wi-Fi Signal. With this device we could localize a person within 15 meter with just only 0.64 dbm in difference between our RSSI measurement and simulation.